Quantifying sulcal and gyral topography in relation to deep seated and ventricular lesions: Cadaveric study for basing surgical approaches and review of literature. (December 2014) - Sampath, Raghuram; Katira, Kristopher; Vannemreddy, Prasad; Nanda, Anil
Abstract Objective. Numerical implication of sulcal and gyral topography for surgical approaches has not been studied. Methods. Percentage gain of distance using sulci as compared to that of gyri was calculated by measuring distances toward the ventricles in 15 hemispheres. Results. Superior frontal sulcus was closest proving greater than 50% gain in distance compared to superior frontal gyrus; inferior temporal sulcus provided greater gain in the temporal lobe. Conclusion. Sulci provide upto 58% distance gain. For trans-gyral approaches, MFG and ITG were found closer to the respective ventricular area.